AI - Nomen Omen / Dr Piermauro Catarinella - Catarinella, Piermauro (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
These days everyone seems to be talking about Artificial Intelligence (AI), presented as something useful and beneficial. Not only will it change our lives, but it is also a reality that we will no longer be able to avoid. AI is easily accessible, and it is easy enough to sign up for a free account (Mosca, 2023). AI can be used as a vocal search engine, to answer questions or messages. It could also be used to create stories, scientific documents and professional photos; as well as to write articles, multi-lingual program codes, and research/degree thesis. AI could also translate written texts, summarize voice dialogues, solve math equations, compose songs, recognize different kinds of voices, control appliances, make phone calls, read forecasts, and give roads guidance. It could also foresee potential risks, threats or dangers, offer customers' support, handle online shares trading, improve profits, and much more (Ellena, 2023).